Immunological imbalance between IFN-³ and IL-10 levels in the sera of patients with the cardiac form of Chagas disease - Daniela A D'Ávila; Paulo MM Guedes; Ana M Castro; Eliane D Gontijo; Egler Chiari; Lúcia MC Galvão (Memorias do Instituto Oswaldo Cruz, 2009)
The immune response is crucial for protection against disease; however, immunological imbalances can lead to heart and digestive tract lesions in chagasic patients. Several studies have evaluated the cellular and humoral immune responses in chagasic patients in an attempt to correlate immunological findings with clinical forms of Chagas disease. Moreover, immunoglobulins and cytokines are important for parasitic control and are involved in lesion genesis. Here, cytokine and IgG isotype production were studied, using total epimastigote antigen on sera of chagasic patients with indeterminate (IND, n = 27) and cardiac (CARD, n = 16) forms of the disease. Samples from normal, uninfected individuals (NI, n = 30) were use as controls. The results showed that sera from both IND and CARD patients contained higher levels of Trypanosoma cruzi-specific IgG1 (IgG1) antibodies than sera from NI. No difference in IgG2 production levels was observed between NI, IND and CARD patients, nor was a difference in IL-10 and IFN-³ production detected in the sera of IND, CARD and NI patients. However, IND patients displayed a positive correlation between IL-10 and IFN-³ levels in serum, while CARD patients showed no such correlation, indicating an uncontrolled inflammatory response in CARD patients. These findings support the hypothesis that a lack of efficient regulation between IFN-³ and IL-10 productions in CARD patients may lead to cardiac immunopathology.